Design of a university model of labor linkage and support for academic management - González Conejo, Franky (2021)
This essay aims at designing a university employment model. The author analyzes four state universities and job opportunities for its graduates through theoretical-practical perspectives and career guidance. It is estimated that this proposed model could have positive effects in the approach of the uncertainties that university students face due to increasing oversupply of professionals. A possible disparity with the requirements of the labor market reflect less favorable indicators which ensures a lack of a single discipline in order to research or intervene the phenomenon labor insertion, as well as the unavoidable bond between the employment sector and the university. The proposed model could, therefore, serve as valuable input for other academic institutions, mainly Latin American universities given the contextual similarity which also strives to improve career guidance for its university students and graduates and provide a quality management process for its majors.